O przyczynach i instrumentach ekologizacji działań ekonomicznych - Kośmicki, Eugeniusz (Wydział Prawa i Administracji UAM, 1986)
Problems of market mechanisms concern also ecologization of economic activity. Previously adopted administrative measures (in the forms of orders and interdictions) proved to be very ineffective. On the other hand, economic mechanisms used in the market economy countries are more efficient than pure administrative measures. In case of a lack of general economic and legal framework of ecologization, the market mechanism contrubutes to the degradation of environment. The elements of enviroment, defined as the so-called „free-goods", have no price whatsover and that leads to their wasting. The economically effective ecologization is possible only when there is an uncontrolled (by enterprises) pressure on the improvement of economic effectiveness. The ecologization costs cannot be then imposed over consumers. The State has many instruments to affect the ecologization of economy at its disposal. Fees have the most typical market character, while environmental norms are of administrative nature. Subsidies of various kinds, supporting research on new technologies are also treated as economic instruments of ecologization, costs of the ecologization are borne then by the whole society. Ecologization creates the largest burden for small and medium enterprises. State preferred environmental norms and subsidies are usually advantageous precisely for enterprises. The effective ecologization in the socialist States requires proper- forming of economic and legal relations and a definite general effectiveness of the economic system. The efficient ecologization is related to maikinig the very enterprises interested in ecological problems, what is possible by means of including ecological tasks to the activity of enterprises, along with productional targets.
On reasons and instruments of ecologization of economic activity